Advances in Fine Needle Aspiration Cytology for the Diagnosis of Pulmonary Carcinoma - Hasanovic, Adnan (SAGE-Hindawi Access to Research, 2011)
New developments in the field of thoracic oncology have challenged the way pathologists approach the diagnosis of pulmonary carcinoma. Nonsmall cell carcinoma is no longer an adequate diagnostic category. Pathologists are required to further classify tumors into adenocarcinoma and squamous cell carcinoma since specific therapies are now recommended depending on the histological tumor type. This change occurred following the discovery of specific molecular alterations that predict response to certain drugs and now molecular testing of tumor cells is often requested to direct therapy. The vast majority of lung cancer is diagnosed in advanced clinical stages, where cytologic or small biopsy material is the only form of tissue diagnosis, thus placing cytology, especially fine needle aspiration biopsy in the front line for management of patients with lung cancer. In this paper we will review the current concepts in the suitability and accuracy of fine needle aspiration biopsy, including diagnosis, classification, prognostic markers, and use of ancillary techniques.